CARICOM system : basic instruments - Pollard, Duke E. (Caribbean Law Pub. Co. KingstonJM, 2003)
Describes briefly the main features of the original Caribbean Community and its successor organisation together with some of the major regional and international developments which impact negatively or positively on their institutional configuration. Focuses on the background of some other high profile institutions and organisations of the CARICOM system as a general introduction to the brief legal analyses of the constituent instruments.